Differentiation of larvae and pupae of aquatic genera of Nearctic Hemerodromiinae (Diptera: Empididae) - Brammer, Colin A.; Harkrider, J. Robert; Macdonald, John F. (Zootaxa, 2009)
Larvae and pupae representing four genera of aquatic dance flies, Chelifera Macquart, Hemerodromia Meigen, Metachela Coquillett, and Neoplasta Coquillett (Diptera: Empididae: Hemerodromiinae) are differentiated, diagnosed, illustrated, and keyed. Results are based on: limited rearing associations of larvae, pupae, and adults; external morphology of larvae, pupae, and pupal exuviae; and fragment sizes of ribosomal DNA extracted from larvae, pupae and adults of Nearctic Hemerodromiinae. Fragment size of ribosomal DNA is diagnostic at the generic level.